2015
DOI: 10.1111/apt.13215
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: opportunistic infections and malignancies during treatment with anti‐integrin antibodies in inflammatory bowel disease

Abstract: Summary Background Anti‐integrin antibodies are effective therapies for Crohn's disease (CD) and ulcerative colitis (UC). However, these drugs carry theoretical risks of opportunistic infection and malignancy. Aim To pool data from all placebo‐controlled studies, to estimate risk of opportunistic infection or malignancy with anti‐integrin antibodies. Methods MEDLINE, EMBASE and the Cochrane central register of controlled trials were searched (up to December 2014). Randomised placebo‐controlled trials of anti‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 46 publications
1
33
0
8
Order By: Relevance
“…Infections including serious infections were also more common in vedolizumab treated patients in the pivotal trials. One meta‐analyses comparing natalizumab, vedolizumab and etrolizumab reported higher absolute numbers of opportunistic infections with these anti‐integrin antibodies, but this difference was not statistically significant . There is also a new case report of pseudomonas meningitis associated with vedolizumab treatment for CD .…”
Section: Discussionmentioning
confidence: 99%
“…Infections including serious infections were also more common in vedolizumab treated patients in the pivotal trials. One meta‐analyses comparing natalizumab, vedolizumab and etrolizumab reported higher absolute numbers of opportunistic infections with these anti‐integrin antibodies, but this difference was not statistically significant . There is also a new case report of pseudomonas meningitis associated with vedolizumab treatment for CD .…”
Section: Discussionmentioning
confidence: 99%
“…To date these are centred upon drug therapy, including 5‐aminosalicylates, glucocorticosteroids, immunomodulator therapy, and biological agents . However, some of these treatments are costly, or are associated with serious adverse events . As a consequence, alternative therapies, aimed at treating disease activity via manipulation of the enteric flora may be of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using vedolizumab as a maintenance agent after corticosteroid induction, vedolizumab may be considered in patients with primary non-response to anti-TNF induction or in patients who develop secondary non-response to one or more anti-TNF agents. Finally, vedolizumab may be considered in patients with a history of infectious, paradoxical autoimmune, and malignant complications on other immune suppressants or biologic agents, in patients with prior malignancy, or in patients at increased risk for infection such as older patients since gut selective anti-integrin antibodies were not associated with an increased risk of infection (RR 1.6, 95% CI 0.2 – 14.8) in a meta-analysis of placebo-controlled anti-integrin trials 45 .…”
Section: 0 Conclusionmentioning
confidence: 99%
“…One meta-analysis included data from 12 trials (4 natalizumab, 6 vedolizumab, 2 etrolizumab) and found that the risk of developing an opportunistic infection was not increased with either gut-specific (RR 1.6, 95% CI 0.2 – 14.8) or gut-nonspecific (RR 2.3, 95% CI 0.1 – 108) anti-integrin agents 45 . Gut-specific (RR 0.8, 95% CI 0.2 – 4.0) and gut-nonspecific (RR 1.6, 95% CI 0.2 – 12.7) anti-integrin agents were not associated with higher rates of malignancy 45 . Large prospective studies will, however, be required to more clearly establish risk of infectious complications and malignancy in patients treated with anti-integrin agents for extended periods of time.…”
Section: 0 Conclusionmentioning
confidence: 99%